GC-MS DETERMINATION OF BIOACTIVE COMPONENTS OF THREE TRAITS OF VILVAM (BAEL) - VN, Ariharan; K, Kalirajan; P, Nagendra Prasad (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Vilvam is an important medicinal plant, which is used to treat many ailments of human beings in the traditional system of medicine. As one of the important conservation aspect of traditional medicinal plant, it is mostly grown in the Hindu Siva temples, where the leaves are mostly used for pooja purpose and medicinal aspects. Based on the morphological features of the leaves, three different traits of plants were identified and selected for the study. This study aimed to screen the phytochemical compound present in the three traits of Vilvam by gas chromatography-mass spectrometry (GC-MS) method. The GC-MS analysis revealed that the phytochemical components present in the trait 1 is different from the other two traits. The trait 2 and 3 are having almost similar components. Among them, trait 3 has more number of bioactive compounds, which can be exploited for the medicinal use in the future. Keywords: Gas chromatography-mass spectrometry, Medicinal plant, Ethnobotany, Vilvam.